ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA DITINJAU BERDASARKAN KEMAMPUAN MATEMATIKA - Safiil Maarif; Rifka Lailatur Rivabiiya (Prodi Pendidikan Matematika FKIP Universitas Madura, 2021)
The purpose og this study was to describe the critical thinking skills of students with high, medium, and low math abilities in solving math problems. This research is a qualitative descriptive study. The subjects of this study were 3 students of class XI MIPA at SMA Negeri Ngoro Jombang, with categories of high, medium, and low mathematical abilities. Methods of data collection in this study using the method of tests and interviews with the main instruments of the researchers themselves and supporting instruments in the form of test sheets for the ability to think critically in mathematics and interview guidelines. Checking the validity of the research data was done by triangulating time. Data analysis techniques are carried out by reducing, presenting data, and make conclusions The results of this study reveal that the indicator of the ability to think critically in mathematics in solving math problems was that students present the information that was known and what requested from the questions correctly, presents information that had not been clearly stated in the questions and the information needed to solve the problems, presents conclusions of concepts / ideas that are relevant to solving the problem, and presenting the steps for completion in a coherent and correct manner and presenting the correct result of solving the problem. The ability to think critically in mathematics of students who have high abilities in solving questions is able to meet all indicators of critical thinking skills, students who are able to think critically in mathematics who are moderate in solving questions are able to meet the three indicators of critical thinking abilities because students are unable to present the correct results, while the ability critical thinking mathematics students with low ability to solve problems are only able to meet two indicators of critical thinking skills, namely students are only able to present the information that is known and the things that are requested from the questions correctly, presenting information that has not been clearly stated in the questions and the information needed to solve the problem.